Analisis Potensi Erosi Sub Das Galugua Kecamatan Kapur IX Menggunakan Pendekatan Universal Soil Loss Equation (USLE) - Hafiz Catur Anggoro; Imam Suprayogi; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Over the function land and the distribution of vegetation in the sub-DAS Galugua give the phenomenon of erosion and sedimentation of land that is not balanced. Model USLE with the help of SIG in use to predict his large erosion and sedimentation of the land. erosion results show the erosion that occurs on the sub-DASGalugua classified in low-grade between 15 to 16 tons/ha/year. the total erosion occurs in sub-DAS Galugua of 4.850,98 tons/year smaller than the value of the transport capacity that is 132.590,76 tons/year, So all the results of erosion transported enter into river and not going on his sedimentation of the land in the sub DAS Galugua.Keywords: land conversion, sedimentation, land erosion, USLE, SIG.